Early Life-History Dynamics of Caribbean Octocorals: The Critical Role of Larval Supply and Partial Mortality - Martínez-Quintana, Ángela; Lasker, Howard R. (Frontiers in Marine Science, 2021)
Recruitment is a key demographic process influencing the dynamics of local populations and recovery following disturbance. For colonial marine benthic taxa, spatial and temporal heterogeneity of recruit distributions is influenced by variation in larval supply, settlement rate and post-settlement survival. Differences in post-settlement survival between the single individuals that initially settle and the small colonies they rapidly develop into, affects recruitment patterns, and studies assessing this ecological process that do not incorporate these different astogenetic stages provide an incomplete understanding of early life-history events. We studied octocoral recruitment dynamics and assessed the roles of pre-settlement, settlement and post-settlement processes in driving recruitment, and distinguished processes occurring to single-polyps and to colonial recruits. We combined fine-scale temporal observations of settlers, with experiments on settlement tiles, and we followed the fates of colonial recruits with different morphological traits for 3 years. We found that the major contributor to single-polyp recruit densities, and ultimately to colonial recruit densities, was larval supply. Single-polyp recruitment was not limited by the availability of free space, settlement cues, or early post-settlement survival. Height was the only predictor of survival and growth after single polyps develop into colonies. Potential growth rates increased with recruit height, but large recruits often suffered partial mortality, distorting the relationship between recruit age and size, and causing most recruits to remain in the recruit size class (≤ 5 cm) longer than a year. Octocorals have been resilient to the conditions that have driven the decline of scleractinian corals throughout the Caribbean, and recruitment has been a key to that success. Our results are crucial to understand early-life history dynamics of Caribbean octocorals, and highlights the need to standardize the definition of recruit among colonial and modular taxa to facilitate inter-specific comparisons, avoid bias in the assessment of population growth, and understand changes in coral reef community assemblages.